2022
DOI: 10.3390/jcm11020303
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Wearing a Medical Mask on the Masticatory and Neck Muscle Activity in Healthy Young Women

Abstract: The objective of this study was to analyze the influence of wearing a medical mask on masticatory and neck muscle activity in healthy young women. We recruited 66 healthy women aged from 18 to 30 years (mean 23.6 ± 2.3 years). The temporalis anterior (TA), the superficial part of the masseter muscle (MM), the anterior bellies of the digastric muscle (DA), and the middle part of the sternocleidomastoid muscle (SCM) potentials were recorded at rest and during functional activity using an eight-channel device for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…sEMG electrodes (Ag/AgCl) with a conductive surface of 16 mm (SORIMEX, Torun, Poland) were placed bilaterally on the skin, covering the examined muscle groups. Four pairs of masticatory and neck muscles were analyzed: temporalis muscle (the anterior part-TA), the masseter muscle (the superficial part-MM), the digastric muscle (the anterior belly-DA), and the sternocleidomastoid muscle (the middle part-SCM), according to the SENIAM (surface EMG for noninvasive assessment of muscles) standards and our previous work [ 28 , 29 ]. The reference sEMG electrode was put on the forehead in the middle of the frontal bone [ 30 ] ( Figure 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…sEMG electrodes (Ag/AgCl) with a conductive surface of 16 mm (SORIMEX, Torun, Poland) were placed bilaterally on the skin, covering the examined muscle groups. Four pairs of masticatory and neck muscles were analyzed: temporalis muscle (the anterior part-TA), the masseter muscle (the superficial part-MM), the digastric muscle (the anterior belly-DA), and the sternocleidomastoid muscle (the middle part-SCM), according to the SENIAM (surface EMG for noninvasive assessment of muscles) standards and our previous work [ 28 , 29 ]. The reference sEMG electrode was put on the forehead in the middle of the frontal bone [ 30 ] ( Figure 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Bioelectric muscle activity was measured during the resting mandibular position (10 seconds), maximal voluntary clenching in the intercuspal position (as hard as possible; 3 × 3 seconds, 2 seconds break), maximal voluntary clenching on dental cotton rollers (as hard as possible; 3 × 3 seconds, 2 seconds break), and maximal mouth opening (as wide as possible; 3 × 3 seconds, 2 seconds break). The averaged results from three measurements were used in the statistical calculations [ 16 , 29 ]. An open eye and closed-eye test were conducted with a 5-minute break between tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we previously reported, wearing a medical mask influences the resting activity of the temporalis anterior and masseter muscles in healthy young women [ 10 ]. However, our research did not analyze subjects with stomatognathic dysfunctions, such as temporomandibular disorders (TMDs).…”
Section: Introductionmentioning
confidence: 99%
“…While TMD and its multifactorial pathoetiology are related to facial morphology, dental occlusion, and psychological and neuromuscular disease, the authors suggest adding mask-related repetitive jaw movements into consideration of the management of TMD as a psychosocial factor. Although a contradictory finding was reported that they found significant decrease in resting temporalis anterior and masseter muscle activity during mask wearing, the observation was only made throughout a period of 4 hours, and only healthy, young females were included in the study, 3 making it insufficient to draw a conclusion on correlation between mask wearing and muscle activity.
Figure 1 Temporomandibular joint activities during frequent mouth opening and protrusive jaw movement for frequent mask adjustment (created with BioRender.com ).
…”
mentioning
confidence: 98%